Study of simple and complex structures in composite materials - Gamito, Simão Pedro Brissos Sousa Jesus (2024)
Abstract The use of composite materials has been increasing exponentially in various engineering fields, not only in fiber-based materials but also in advanced particle composites, such as Functionally Graded Materials (FGM). This work focuses on fiber-based materials, which, by considering the appropriate fiber direction within each layer, can achieve different mechanical properties, leading to widespread use. However, due to the heterogeneous and orthotropic nature of these materials, failure prediction becomes challenging. Combining analytical methods (often using symbolic computing platforms) and/or numerical methods allows for failure prediction. Despite using a single or combined method approach, verifying the results with alternative references is crucial. This study aimed to develop and implement a numerical-analytical and experimental approach to characterize the mechanical behavior of fiber-based composite plates with an epoxy matrix. The study considered carbon fiber/epoxy plates with varying numbers of layers and fiber orientations. Four approaches were employed: the first and second approaches, based on the Finite Element Method (FEM) using ANSYS Mechanical Parametric Design Language (Mechanical APDL) and ANSYS WORKBENCH, respectively; the third approach involved analytical results obtained through the MAPLESOFT symbolic computing software; the fourth approach relied on experimental tensile tests of the composite plates, using strain gauges to measure resulting strains from a bi-axial tensile device. Additionally, a three-dimensional static study of a triathlon guide was calculated using Solidworks Simulation FEM software. The results indicate that while some numerical methods can predict failure in composite materials with reasonable accuracy, this prediction is fundamentally linked to the failure criterion used in the analysis.